Britain at a Loss - Elena Ananieva (Научно-аналитический вестник Института Европы РАН, 2018)
. Intra- and interparty struggles in the UK over Brexit somewhat overshadowed the public opinion until the People’s Vote march in London (20 October 2018). Opinion polls show that the UK public is divided on the Brexit strategy and the political elite is distrusted